Kolaborasi Pemberdayaan dan Pendampingan UMKM Desa: Pemanfaatan Platform Digital terhadap Kemandirian Ekonomi Masyarakat UMKM Desa Klagen - Naura Bilqis Tasyakurina; Salva Wi Nur ain; M. Dedy Marhadi; M. Sulthan Alvi; Chrystia Aji Putra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Technology is developing rapidly and continues to change various aspects of human life, including the economic and business sectors. Some humans continue to compete to utilize this technology to stay in the flow of world development for their survival. Through the utilization of digital platforms, MSMEs in Klagen village are one example of followers of technological developments that allow the village to be empowered and supported to increase its economic independence. This research aims to improve the ability of MSMEs to utilize digital platforms to expand markets and increase revenue because business development in Klagen Village is hampered by the lack of technological expertise and digital marketing among MSMEs. The method used in this research is participatory with a community organizing approach. The MSMEs selected for mentoring were then interviewed in detail and evaluated as part of the research strategy. With this mentorship, it is expected that MSME players can successfully penetrate larger markets, increase sales, and optimize digital marketing.